2013
DOI: 10.1111/jcpp.12016
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent subthreshold‐depression and anxiety: psychopathology, functional impairment and increased suicide risk

Abstract: Subthreshold-depression and subthreshold-anxiety are associated with an increased burden of disease and suicide risk. These results highlight the importance of early identification of adolescent subthreshold-depression and anxiety to minimize suicide. Incorporating these subthreshold disorders into a diagnosis could provide a bridge between categorical and dimensional diagnostic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
259
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(278 citation statements)
references
References 46 publications
14
259
0
5
Order By: Relevance
“…The multi-centre Saving and Empowering Young Lives in Europe (SEYLE) study reported that 5.8% of participants met criteria for an anxiety disorder, 10.5% met criteria for depressive disorder [15], while 32.3% reported suicidal thoughts [16]. In this study we examined physical activity and its associations with mental health indicators in the SEYLE sample.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-centre Saving and Empowering Young Lives in Europe (SEYLE) study reported that 5.8% of participants met criteria for an anxiety disorder, 10.5% met criteria for depressive disorder [15], while 32.3% reported suicidal thoughts [16]. In this study we examined physical activity and its associations with mental health indicators in the SEYLE sample.…”
Section: Introductionmentioning
confidence: 99%
“…One recent meta-analysis found the worldwide prevalence of depressive disorder in youth to be 2.6 % (Polanczyk et al 2015), with other work showing about one third of adolescents manifesting subthreshold depression (Balazs et al 2013). Both adolescent subthreshold depression and depressive disorder are associated with severe functional impairments (Fröjd et al 2008), elevated rates of substance abuse (Diego et al 2003), increased likelihood of adult depression (Pine et al 1999), and poor physical health (Naicker et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both adolescent subthreshold depression and depressive disorder are associated with severe functional impairments (Fröjd et al 2008), elevated rates of substance abuse (Diego et al 2003), increased likelihood of adult depression (Pine et al 1999), and poor physical health (Naicker et al 2013). Another severe consequence of adolescent depression is suicide (Wild et al 2004), with more than half of adolescent suicide victims having a depressive disorder at the time of death (Thapar et al 2012), and subthreshold-depressed adolescents being three times more likely to have suicidal thoughts/ideations than their non-depressed counterparts (Balazs et al 2013). Given these data on the prevalence and consequences of adolescent depression, identifying its etiological mechanisms is critical for developing empiricallybased prevention and intervention programs (Garber 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Se calcula que la prevalencia de vida entre los 13 y los 18 años es de 14,3% para los trastornos del estado de ánimo y de 31,9% para los trastornos de ansiedad (Merikangas et al, 2010). Esta estimación tiene en cuenta exclusivamente los casos de trastorno franco, a los que debemos adicionar los estados de malestar subclínicos (Balázs et al, 2013).…”
unclassified